A single tax on land, pro and con - Davis, Kary Cadmus (My University, 1891)
Introduction: In discussing an economic question, which, like the one named in the above title, suggests a radical change to be made in the affairs of civil government, it is of special importance to know that there are evils existing which the change advocated is intended to correct. The chief advocates of a single tax on land claim for it that it is a remedy for the present depressed condition of the laboring classes. The scarcity of employment, the depression of wages to the starvation point, the stagnation of capital,—these conditions of society, shamefully glaring the nineteenth century civilization in the face, it is claimed the single tax system would remedy.
Citation: Davis, Kary Cadmus. A single tax on land, pro and con. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Single tax; Capitalism; Money; 19th century; Depression; Theses; Manuscripts (documents)